(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2024)
The background of this research is the lack of interest of Dhyana Pura University Informatics Engineering Study Program students in visiting the library. This shows the need for a new innovation in the library that can increase the attractiveness of students to visit the library more often. The purpose of this study was to implement augmented reality with the Android-based marker-based tracking method in the search system for reference books for IT courses in the UNDHIRA library, to find out the results of the analysis of the level of user convenience and satisfaction in using the application, as well as to find out the results of a comparison of the level of interest in student visits to the library before and after system implementation. This research is a quantitative study; the data was collected using a questionnaire technique on 54 application users. The results showed that the usability of the application was 87.41% or could be classified as "very good." The results of the Kano model test show that the attributes of the application are very satisfying to users, with the majority of the attributes in the application being included in the attractive category. The results of a comparative analysis of the interest level of student visits to the library before and after system implementation showed that 49 out of 54 students stated that the application could increase their interest in visiting the library. So based on these results, this application can increase the interest of IT students in visiting the library.